External auditors' reliance on internal auditors and its impact on external auditors' independence: Evidence from Algerian audit environment - Ouaker meriem,; Ayadi abdelkader,; Ouaker hanane, (Journal of North African Economies, 2025)
This study investigates the external auditor (EA) reliance on internal audit’s work and its impact on external auditors' independence. The study employs a mixed method comprising a survey‐based factorial experiment in addition to semi‐structured interviews. The results, based on 55 fully‐crossed factorial experiments with EAs, show that external auditors’ reliance on internal auditors work has a significant impact on external auditor’s independence by influences on both external auditor’s mental and virtual independence, and external auditor’s mandatory change, and has no significant impact on providing advisory services.